2020
DOI: 10.9734/ajgr/2020/v3i130096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flood on Food Security, Livelihood and Socio-economic Characteristics in the Flood-prone Areas of the Core Niger Delta, Nigeria

Abstract: The study examined the effects of flood risk levels on food security, livelihood and socio-economic characteristics in the flood-prone areas of the core Niger Delta, Nigeria using a descriptive survey design and 790 respondents were selected with the aid of a multistage stratified sampling technique in Bayelsa, Delta and Rivers States, representing the core Niger Delta. Descriptive statistics were used in the analysis and presentation of data. The findings of the study showed that 75.3% of the respondents agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…It is one of the 10 countries most vulnerable and at risk of food insecurity due to climate change, economic crises, and conflict (World Food Programme 2020). It experiences annual flooding in many of its states and the impact on its food security is widely acknowledged (Durodola 2019;Metu et al 2016;Week and Wizor 2020). In July 2021, the country's president blamed flooding for the rising food insecurity (Ogundele 2021).…”
Section: Flooding Food Security and The Nigeria Agriculture Promotion...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the 10 countries most vulnerable and at risk of food insecurity due to climate change, economic crises, and conflict (World Food Programme 2020). It experiences annual flooding in many of its states and the impact on its food security is widely acknowledged (Durodola 2019;Metu et al 2016;Week and Wizor 2020). In July 2021, the country's president blamed flooding for the rising food insecurity (Ogundele 2021).…”
Section: Flooding Food Security and The Nigeria Agriculture Promotion...mentioning
confidence: 99%
“…In July 2021, the country's president blamed flooding for the rising food insecurity (Ogundele 2021). Although other factors impact food security, ranging from insecurity (which prevents farmers access to their lands) to communal clashes among farmers and herdsmen (Echendu 2021a;Furini 2019;Kralovec 2020;Lawal 2020;Ogundipe et al 2020), flooding remains a top factor (Chukwu 2014;Madukwe et al 2019;Week and Wizor 2020). Agriculture, fisheries, and aquaculture, the primary food sources in Nigeria, are all negatively affected by flooding.…”
Section: Flooding Food Security and The Nigeria Agriculture Promotion...mentioning
confidence: 99%
“…It makes it difficult to take care of family members, especially children. In addition, those living in floodprone areas face poor living conditions (Week & Wizor, 2020).…”
Section: ⅱ Literature Reviewmentioning
confidence: 99%
“…The yearly occurrence of flooding in the core Niger Delta has led to the devastation or destruction of a large expanse of land including cultivated farmlands like that witnessed in Kolaware Community in Patani Local Government Area of Delta State were the 2018 flooding incidents led to the loss of their major crops like yam, plantain, okra and cocoyam. Also, the extent of the flood that occurred in Akinima community in Ahoada West Local Government Area of Rivers State led to the destruction of crops like plantain, cassava and banana [11]. Interestingly, it is important to state categorically that flood hazard in the core Niger Delta is real.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it is important to state categorically that flood hazard in the core Niger Delta is real. Wizor and Week [11] revealed that food security, livelihood and socio-economic characteristics of flood-prone areas of the core Niger Delta has been negatively impacted by flooding particularly with regards to the destruction of farmlands and other sources of livelihood leading to food insecurity, income reduction, and poor livelihood among the residents of the core Niger Delta States.…”
Section: Introductionmentioning
confidence: 99%